Effectiveness of Soybean (Glycine max) Extract Dosages on Sperm Motility of Pangasius pangasius Stored Under Preservation Temperature - Cut Lutfina Putri; Suri Purnama Febri; Teuku Fadlon Haser; Lilis Nurjanah; Shadiqa Malahayati; Ika Rezvani Aprita; Suraiya Nazlia (Fakultas Pertanian Universitas Samudra, 2025)
This study aims to analyze the effectiveness and determine the dosage of soybean extract that can increase the motility of catfish sperm stored at preservation temperature. The research method used is RAL (Completely Randomized Design) with 4 treatments 3 replications where P1 0 ml soybean extract / 1 ml sperm, P2 0.3 ml soybean extract / 1 ml sperm, P3 0.6 ml soybean extract / 1 ml sperm, and P4 0.8 ml soybean extract / 1 ml sperm. The pH of catfish sperm before and after mixing soybean extract is 8. While after cryopreservation, the pH in treatment P1 is 5, treatments P2 and P4 are 6, and in treatment P3 with a value of 7. The volume of sperm used in treatments P1, P2, P3, and P4 before being diluted is 3 ml. The color of catfish sperm in P1 is milky white, while in P2, P3, P4 the color of the sperm is cream and smells fishy. Meanwhile, the viscosity level in P1 was thick, P2 was thin, and P3 and P4 were liquid. The results of observations of catfish sperm motility obtained the best value in treatment P3 (0.6 ml of soybean extract/1 ml of sperm) with a value of 2.6 (good). Meanwhile, the worst motility value was obtained in treatment P1 (without the addition of extract) with a motility value of 0.6, which is considered poor.